Medicinal properties of Abutilon Indicum - S Rajeshwari; SP Sevarkodiyone (Open Journal of Plant Science - Peertechz Publications, 2018)
Abutilon indicum is a common Indian shrub, belonging to the family Malvaceae; Also known as Mallow in english, Abutilon indicum is used as a medicinal plant. It has been extensively used as a traditional medicine as a laxative, emollient, analgesic, anti-diabetic, anti-inflammatory and blood tonic agent and also in the treatment of leprosy, urinary disease, jaundice, piles, relieving thirst, cleaning wounds and ulcers, vaginal infections, diarrhea, rheumatism, mumps, pulmonary tuberculosis, bronchitis, allergy, blood dysentery, some nervous and some ear problems. Various studies on the plant extract have been performed to confirm the anti-oxidant, anti-bacterial, analgesic, anti-inflammatory, anti-cancer, hepato-protective, immuno-modulatory and larvicidal activities of the plant. This plant is often used as a medicinal plant and is considered invasive on certain tropical islands. In traditional medicine, A. indicum is used as a aphrodisiac, demulcent, diuretic, laxative, pulmonary and sedative (leaves). The bark is astringent and diuretic; laxative, expectorant and demulcent (seeds); laxative and tonic, anti-inflammatory and anthelmintic (plant); analgesic (fixed oil); diuretic and for leprosy (roots). The plant is very much used in Siddha medicines. In fact, the bark, root, leaves, flowers and seeds are all used for medicinal purposes by Tamils. The leaves are also used to treat for pile complaints. The flowers are traditionally used to increase semen in men. The phytochemical analysis showed the Presence of Alkaloid, Saponins, Amino acid, Flavonoids, Glycosides and steroids. This plant exhibits several potential pharmacological activities. A review on the various studies on the plant has been provided for the purpose of understanding its medicinal properties.